Freedom of Expression of the Visionary State in the Modernism Poetry - Калашник, Ольга Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is dedicated to the visionary poetry of the Modernism period. The author raises the issue of theoretical comprehension of literary visionarism as 1) a vision genre and an artistic method, which is an established opinion in literary studies; and 2) an embodiment of the author's actual visionary experience (mystic feeling). The latter focuses on the special role of language, which, through its associative power, becomes the subject of art [of poetry], while demonstrating an almost irrationality of the writing process. The article argues that the ability of poetic language to accurately express the dynamics of the visionary state derives from the freedom of art which poets have been searching ever since the Romanticism and had managed to grasp during the Modernism period. The manifestations of this freedom through experiments with rhythm, the phenomenon of silence, looseness of metaphor, associativity etc. are reviewed via the interpretations of the 20th century Ukrainian poetry. The image and symbolic content of the poetry is investigated from the point of visionary experience (infernal and beatific visions). Methods of visionary experiences' expression with and without a  lyrical subject are demonstrated